The Mediating Effect of Work-Life Balance between Motivation and Job Satisfaction and Its Impact on Emotional Intelligence of Mystery Shopping Professionals - Anand Shankar Raja Manivannan (SEISENSE Journal of Management, 2019)
Purpose- Enhancing job satisfaction through motivation and Work-Life Balance (WLB) and checking the overall impact on Emotional Intelligence of mystery shopping professionals is the aim of this research. The work depends on factors such as sudden demand, high workload, on-time submission of assignments, a new area for exploration and fluctuation in pay scale. Design- The data were collected from mystery shopping professionals through social media platform using a questionnaire link (N=338). The sampling technique employed in this study was a convenient sampling technique. CFA (Confirmatory Factor Analysis) using AMOS software was performed. The questionnaire instrument SSREI, GJSS, WEIMS and (Tasdelen’s WLB) were adopted for this study. Findings- The study revealed that motivation has a positive impact on Work-life balance and intern enhances the job satisfaction of mystery shoppers. However, the overall impact on EI is negative. The Goodness of Fit Index such as (AGFI, NFI, TLI, CFI, RMSEA, RMR, and AVE) indicates a good fit of the Structural Equation Model. Originality/Value: The study reflected on the four essential concepts, which has evolved in the domain of HRM and OB for many years. In the context of mystery-shopping professional, it has been used and the recommendations will help the market research agencies and the mystery shoppers. Exploring Work-Life Balance (WLB) as a mediating variable between motivation and Job satisfaction and the overall impact on EI of mystery shopping professionals is a new insight.